Prevalence and Effect of Workplace Violence against Emergency Nurses at a Tertiary Hospital in Kenya: A Cross-Sectional Study - Betty Kiunga Kibunja; Horatius Malilu Musembi; Rachel Wangari Kimani; Samwel Maina Gatimu (Elsevier, 2021)
Introduction: Workplace violence (WPV) is a major occupational and health hazard for nurses. It affects nurses' physical and psychological well-being and impacts health service delivery. We aimed to assess the prevalence and describe the consequences of WPV experienced by nurses working in an emergency department in Kenya. Methods: We conducted a descriptive cross-sectional study among emergency nurses at one of the largest tertiary hospitals in Kenya. We collected data using a structured questionnaire adapted from the 'WPV in the Health Sector, Country Case Studies Research Instruments' questionnaire. We described the prevalence and effects of WPV using frequencies and percentages. Results: Of the 82 participating nurses, 64.6% were female, 57.3% were married and 65.8% were college-educated (65.8%). Participants' mean age was 33.8 years (standard deviation: 6.8 years, range: 23-55). The overall lifetime prevalence of WPV was 81.7% (n = 67, 95% confidence interval [CI]: 71.6%-88.8%) and the 1-year prevalence was 73.2% (n = 63, 95% CI: 66.3-84.8%). The main WPV included verbal abuse, physical violence, and sexual harassment. Most incidents were perpetrated by patients and their relatives. No action was taken in 50% of the incidents, but 57.1% of physical violence incidents were reported to the hospital security and 28.6% to supervisors. Perpetrators of physical violence were verbally warned (42.9%) and reported to the hospital security (28.6%). Conclusion: Workplace violence is a significant problem affecting emergency nurses in Kenya. Hospitals should promote workplace safety with zero-tolerance to violence. Nurses should be sensitised on WPV to mitigate violence and supported when they experience WPV.